(untitled) (Historia, 2021)
It may come as a surprise to readers of this South African journal that post-colonial studies are a comparatively new field of study in the Humanities, especially in literature studies, in Germany. Of course historians have been dealing with Germany’s colonial heritage for decades, yet there were few approaches trying to integrate the account of historical occurrences into the context of a Westernised philosophical concept until the late1980s. Van der Heyden and Zeller’s books aim at dealing with colonialism as a cultural phenomenon, touching on "how colonial discourses influenced the mental and cultural self-image of the former colonial powers and how these discourses contributed to their nation building and their national image" (Van der Heyden & Zeller [2005] from p 8 - reviewer’s translation). Both volumes offer fascinating insights for readers of all backgrounds into better and often lesser known aspects of German colonialism; and while Berlin as the geographical locus is the focus of both works, the various contributions transcend this spatial limitation.